Lokalizacja nowotworów głowy i szyi oraz jej znaczenie dla skutecznej terapii logopedycznej - Kozłowska, Dominika (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The author describes functional disorders of the mouth, throat and larynx after oncological treatment of head and neck cancer. This work presents the significance of the location for undertaking the appropriate speech therapy and the therapy schedule and its most important assumptions. Interdisciplinary treatment of head and neck cancer leads to improved prognosis and survival of patients. However, radical treatment is associated with a significant reduction in the quality of life. In order to obtain the maximum improvement in the quality of life of patients, it is crucial to start speech therapy and physiotherapy during the treatment and continue it after its completion.